1, 5-Naphthalene disulfonate stability and breakdown kinetics in aqueous solutions under geothermal conditions. (March 2021) - Sajkowski, Lucjan; Seward, Terry M.; Mountain, Bruce W.; Marynowski, Leszek
Highlights: 1, 5-Naphthalene disulfonate (1, 5-NDS) thermal breakdown rates have been investigated. 1-Naphthol, 2-naphthol, 1-chloronaphthalene and naphthalene have been detected as breakdown products of 1, 5-NDS at ≥ 200 °C. Breakdown products of 1, 5-NDS have potential use as geothermal tracers. Abstract: Naphthalene disulfonate solutions have been frequently injected into active geothermal reservoirs and their subsequent detection ("recovery") in nearby wells/bore holes used as an indicator of well connectivity. 1, 5-naphthalene disulfonate (1, 5-NDS) has been employed as model compound to investigate the thermal breakdown rates and reaction pathways of naphthalene disulfonates and naphthalene sulfonates in oxygen-free sodium chloride solutions at elevated temperatures. Two series of experiments were conducted using quartz glass ampoules. The first series focused on the 1, 5-NDS breakdown rate in and different salt solutions (i.e. NaCl +/- Na2 SO4, NaHS/H2 S and FeS2 ) at saturated vapour pressure at 250, 270 and 300 °C. The second series focused on 1, 5-NDS breakdown between 200 and 300 °C, for one, two and three weeks at each temperature. Results show that 1, 5-NDS breakdown is temperature-dependent and generates mixture of products. At 200 °C, 1, 5-NDS breakdown forms mainly 1-naphthalene sulfonate (1-NSA), whereas above 250 °C, 1, 5-NDS generated significant amounts of naphthalene (NAP). NAP remains stable at experimental conditions.